The Microbiome in Pancreatic Cancer-Implications for Diagnosis and Precision Bacteriophage Therapy for This Low Survival Disease - Kabwe, Mwila; Dashper, Stuart; Tucci, Joseph (Frontiers in Cellular and Infection Microbiology, 2022)
While the mortality rates for many cancers have decreased due to improved detection and treatments, that of pancreatic cancer remains stubbornly high. The microbiome is an important factor in the progression of many cancers. Greater understanding of the microbiome in pancreatic cancer patients, as well as its manipulation, may assist in diagnosis and treatment of this disease. In this report we reviewed studies that compared microbiome changes in pancreatic cancer patients and non-cancer patients. We then identified which bacterial genera were most increased in relative abundance across the oral, pancreatic, duodenal, and faecal tissue microbiomes. In light of these findings, we discuss the potential for utilising these bacteria as diagnostic biomarkers, as well as their potential control using precision targeting with bacteriophages, in instances where a causal oncogenic link is made.